Incest Survivors' Life-Narratives. (June 2020) - Buchbinder, Eli; Sinay, Dalia
This article analyzes the narratives of survivors of father−daughter incest using 20 in-depth interviews with women, each asked to choose a title for her life-story and reflect on its meaning. Three narratives emerged: "Surviving" tells of a struggle for personal achievement in an independent life alongside intensely traumatic experiences and negative feelings, "Fighting Back/Seeking Vengeance" tells of aspiring to strength by acting on their will to fight back and desire for revenge, and "Growing" reflects the wish to fight and win a place in the world through a "rebuilding" process. The conceptualization of incest survivors' life-narratives is based on the dialectical perspective.